ANALISIS SALURAN PEMASARAN KELAPA SAWIT DI DESA BAKU-BAKU KECAMATAN MALANGKE BARAT KABUPATEN LUWU UTARA - Sumiati Sumiati; Rusida Rusida; Idawati Idawati (Universitas Andi Djemma Palopo, 2017)
The large amount of palm oil production has not reflected the efficient marketing system, especially when viewed from the profit received by farmers. Marketing efficiency term is often used in assessing job performance (performance) marketing process. It reflects a consensus that the implementation process should take place in an efficient marketing. Technology or a new procedure should only be implemented if it can improve the efficiency of the marketing process. Objective of this research is to analyze how oil palm marketing channels in the village of Baku-Baku Malangke Western District of North Luwu. The research method is observation and interviews using a questionnaire. Sampling is done on the basis of a direct approach to respondendengan using slovin formula. Analysis of the data used in this research is to use methods of analysis are obtained deskriptif.Hasil there is one marketing channel Signs Fresh Fruit oil palm farmers or homogeneous with the flow as follows: Farmers Traders Gatherer mills. Oil palm farmers in the village of Bau-Baku Malangke Western District of North Luwu only sell Signs Fresh Fruit to the existing traders, Signs Fresh Fruit distributed by merchants collector to palm oil mill (end consumer). The total cost of the harvest to be incurred by the farmer is Rp 200 / kg. While the benefits received Rp 450 / kg and the farmer gets 72% of marketing channel due to the brevity of existing channels.